4 Renal function-based contrast dosing to define 'prognostic' contrast limits in patients undergoing coronary angioplasty. (25th January 2018) - Chandra, Navin; Nadra, Imad; Ding, Lillian; Hardiman, Sean; Fung, Anthony; Aymong, Eve; Webb, John; Wood, David; Virani, Sean; Chan, Albert W; Vuurmans, Tycho; Hodge, Steven; et al.
Abstract : Background: Renal function-based contrast dosing minimises renal injury following percutaneous coronary intervention (PCI). The ratio ( R ) of contrast volume:glomerular filtration rate (GFR) has been studied but its prognostic relevance is unknown. Aim: To establish the relationship between R and mortality; and define a 'prognostic' threshold ( RT ) for contrast in PCI for stable disease, non ST-elevation ACS (NSTEACS) and ST-elevation ACS (STEACS). Method: We evaluated 44 082 non-dialysis patients between 2008–2014. GFR was calculated using CG, CKD-EPI and MDRD equations. R was determined for each patient and its relationship with mortality was modelled mathematically and analysed using Cox regression and adjusted ROC curve analyses. Results: Multivariable analyses identified R as an independent predictor of 3 year mortality (HR=1.03, 95% CI: 1.02 to 1.04, p<0.001). There was an exponential relationship between R and mortality; for every unit increase in R, 3 year mortality increased by 13%–14% regardless of PCI indication. Adjusted analyses indicated RT was consistently higher in stable disease ( RT =7.7–8.3) compared to NSTEACS ( RT =5.3–5.7) and STEACS ( RT =5.3–5.7). Conclusion: This study advocates a RT =7.7–8.3 for stable disease and RT =5.3–5.7 for NSTEACS/STEACS. This is greater than previously reported but implies greater contrast volumes may ultimately be tolerated in the contemporary PCI era.